Psychological Counseling Students' Attitudes Towards Autism Disorder" A Field Study At Tishreen University" - التزه , شيرين (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the current research is to know the attitudes of psychological counseling students (fifth year) towards autism disorder at Tishreen University, and to know the difference according to gender and place of residence. The sample was a simple random of (51) students. A questionnaire was used to measure attitudes of psychological counseling students towards autism disorder prepared by the researcher, The results showed that (80.4%) of the students had positive attitudes and (19.6%) were neutral, and the results did not show any differences in attitudes according to gender and place of residence.